2014
DOI: 10.1002/2014gl061975
|View full text |Cite
|
Sign up to set email alerts
|

Static stress triggering explains the empirical aftershock distance decay

Abstract: The shape of the spatial aftershock decay is sensitive to the triggering mechanism and thus particularly useful for discriminating between static and dynamic stress triggering. For California seismicity, it has been recently recognized that its form is more complicated than typically assumed consisting of three different regimes with transitions at the scale of the rupture length and the thickness of the crust. The intermediate distance range is characterized by a relative small decay exponent of 1.35 previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…A generic attribute in all these cases is that one event can trigger or somehow induce another one to occur -or possibly numerous further events. One of the most prominent examples of such event-event triggering are aftershocks [32,33,34,35,36,37,13]. Aftershock sequences are characterized by timevarying (local) event rates, which are often empirically found to approximately followacross a wide range of scales and systems from friction and fracture to socio-economic systems [35,38,39,40,41,7,9,10,16,27,28,29,30,31] -the Omori-Utsu (OU) relation,…”
Section: Event-event Triggering and Aftershocksmentioning
confidence: 99%
“…A generic attribute in all these cases is that one event can trigger or somehow induce another one to occur -or possibly numerous further events. One of the most prominent examples of such event-event triggering are aftershocks [32,33,34,35,36,37,13]. Aftershock sequences are characterized by timevarying (local) event rates, which are often empirically found to approximately followacross a wide range of scales and systems from friction and fracture to socio-economic systems [35,38,39,40,41,7,9,10,16,27,28,29,30,31] -the Omori-Utsu (OU) relation,…”
Section: Event-event Triggering and Aftershocksmentioning
confidence: 99%
“…For this purpose, we calculate for all earthquakes in the catalogue, the fraction w of aftershocks which is expected to occur in the study region by means of the empirical probability density distribution recently derived for California seismicity , which has been also found to be in agreement with static stress triggering . Although the spatial distribution function has so far been fitted only to California data, Hainzl et al (2014) showed in their electronic material that the distribution is not strongly dependent on the focal mechanism. Thus we use it for all empirical data.…”
Section: Sequence Selectionmentioning
confidence: 99%
“…Note that this empirical distribution is found to be in agreement with static stress triggering . Although the spatial distribution function has so far been fitted only to California data, Hainzl et al (2014) showed in their electronic material that the distribution is not strongly dependent on the focal mechanism. Thus we use eq.…”
Section: Cluster Selectionmentioning
confidence: 99%